1980
DOI: 10.1002/ajpa.1330520404
|View full text |Cite
|
Sign up to set email alerts
|

Blood groups and types, hemoglobin variants, and G‐6‐PD deficiency among Abu Dhabians in the United Arab Emirates

Abstract: Some erythrocyte genetic factors were studied in the indigenous population of Abu Dhabi, the capital of the United Arab Emirates, on the southeastern coast of the Arabian peninsula. Determinations carried out included blood groups and types ABO, MNS, Rh0, KkJsa, FyaFyb, P1, Lea, Vela, hemoglobin variants, and screening for G-6-PD deficiency. Prevalence of most blood groups and types harmonized with that among neighboring Arabs and some Arabs elsewhere. The MS and NS gene complexes were noticeably high. African… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…One of these was from Abu Dhabi Emirate, and the other was from Um Al-Quwain Emirate, with populations of about 80 000 and 10 000, respectively (Ramahi, 1973). Hb A2 was not raised in any of the people reported here, and a survey on Hb variants only showed Hb S among Abu Dhabians (Kamel et al, 1979).…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…One of these was from Abu Dhabi Emirate, and the other was from Um Al-Quwain Emirate, with populations of about 80 000 and 10 000, respectively (Ramahi, 1973). Hb A2 was not raised in any of the people reported here, and a survey on Hb variants only showed Hb S among Abu Dhabians (Kamel et al, 1979).…”
Section: Discussioncontrasting
confidence: 58%
“…One of these was from Abu Dhabi Emirate, and the other was from Um Al-Quwain Emirate, with populations of about 80 000 and 10 000, respectively (Ramahi, 1973). Hb A2 was not raised in any of the people reported here, and a survey on Hb variants only showed Hb S among Abu Dhabians (Kamel et al, 1979 (Perrine et al, 1972). The patients presented here have been 'selected' in that they were referred patients and their number is obligatorily small because of the small Abu Dhabian population and the relatively low frequency of Hb S gene of0 * 0120 (Kamel et al, 1979 (Phillips, 1971).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Bener and Yousafzai (2014) observed the blood group diversity in the Qatari population and Al- Arrayed et al (2001) reported blood groups distributions in the population of Bahrain. Kamel et al (1980) studied 10 erythrocyte polymorphic systems in the indigenous population of Abu Dhabi, and concluded that the prevalence of most blood groups were consistent with those of neighboring Arabs. Yip et al (2006) carried out genotyping in Kuwaiti subjects and detected the distribution of sub-types of the ABO blood groups.…”
Section: Introductionmentioning
confidence: 93%